Marketing sonified fragrance: Designing soundscapes for scent - Spence, C; Di Stefano, N; Reinoso-Carvalho, F; Velasco, C (SAGE Publications, 2024)
Auditory branding is undoubtedly becoming more important across a range of sectors. One area, in particular, that has recently seen significant growth concerns the introduction of music and soundscapes that have been specifically designed to match a particular scent (what one might think of as “audio scents” or “sonic scents”). This represents an exciting new approach to the sensory marketing of fragrance and for industries with strategic sensory goals, such as cosmetics. Crucially, techniques such as the semantic differential technique, as well as the emerging literature on crossmodal correspondences, offer both a mechanistic understanding of, and a practical framework for, those wishing to rigorously align the connotative meaning and conceptual/emotional/sensory associations of sound and scent. These developments have enabled those working in the creative industries to start moving beyond previously popular approaches to matching, or translating between the senses, that were traditionally often based on the idiosyncratic phenomenon of synaesthesia, toward a more scientific approach while nevertheless still enabling/requiring a healthy dose of artistic inspiration. In this narrative historical review, we highlight the various approaches to the systematic matching of sound with scent and review the various marketing activations that have appeared in this space recently.